Direct Fabrication of Reduced Graphene Oxide@SnO2 Hollow Nanofibers by Single-Capillary Electrospinning as Fast NO2 Gas Sensor. (21st October 2019) - Wang, Dong; Tang, Mingcong; Sun, Jianbo
Abstract : Single-capillary electrospinning has been exhibited to be a simple and scalable method for fabricating nanofibers. Construction of graphene/inorganic fibers with the core-shell hollow structure using graphene as skeleton has been rarely reported. Here, we show a facile approach to prepare electrospun reduced graphene oxide@SnO2 composite nanofibers with the hollow structure. The hollow core@shell structure is formed in a single-capillary electrospinning process including sintering, which is promising for the preparation of graphene/inorganic composite nanofibers. The reduction of as-synthesized graphene is realized by stannous ion. Resulting hollow and core-shell structure enables the reduced graphene oxide@SnO2 composite nanofibers to adsorb and desorb the target gas more easily, which is promising for future applications as fast NO2 gas sensor.